Effectiveness of audiovisual distraction in behavior modification during dental caries assessment and sealant placement in children with autism spectrum disorder - Fakhruddin, Kausar Sadia (Dent Res J (Isfahan), 2017)
BACKGROUND: The aim of this study was to evaluate the effectiveness of audiovisual (AV) distraction in behavior modification during dental caries assessment and sealant placement in children with autism spectrum disorder. MATERIALS AND METHODS: This study was conducted on 28 children diagnosed with autism spectrum disorder, aged 6.5−9.8 years. Children underwent one introductory (desensitization) appointment and three treatment sessions. During the introductory session, children had the procedures explained to them, they watched a movie projected on a screen while oral screening and assessment of cooperation level were carried out. In treatment session I, oral examination, charting, and dental x-rays were undertaken, whereas the children watched movies with or without video eyewear. During treatment sessions II/III, dental prophylaxis was carried out on upper and lower jaws in addition to the application of dental sealants on the right upper and lower and the left upper and lower permanent molars, respectively, while the children were distracted by cartoon movies using video eyewear. Changes in pulse oximeter and heart rate were recorded every 5 min. Independent samples t-test was used to assess the significance of changes in pulse and O(2) saturation levels during each visit. RESULTS: International Caries Detection and Assessment System-code 2 was found to be the most prevalent (n = 58; 52%). A significant difference (P < 0.02) was observed in mean heart rate during dental screening of the upper and lower jaws with and without video eyewear. A decrease was observed in the mean heart rate during subsequent treatment sessions. CONCLUSION: Initial desensitization appointment and “tell-show-do” approach, followed by short and positive treatment sessions, assisted in gaining cooperation and improving behavior in the subjects. Video eyewear distraction proved an effective tool in managing children with autism spectrum disorder during noninvasive preventive dental procedures.